Criteria for sustainable curriculum of TVET teacher education programme in Malaysia - Md Yunos, Jailani; Lai, Chee Sern; Hamdan, Hidayah (Penerbit UTHM, 2019)
The purpose of a Teacher Education programme is to produce quality teachers, especially teachers that can perform the task of teaching effectively and deliver the purpose of the National Education Philosophy, consequently leading to a sustainable TVET Teacher Education programme. One aspect that contributes to the sustainability of a programme is the curriculum. The curriculum has to be able to react with the changes took place in the workplace especially for a developing country like Malaysia. Hence, this study was carried out to explore the criteria for the sustainable curriculum of TVET Teacher Education programmes in Malaysia. A qualitative research approach was used for this study, and semi-structured interviews were conducted with 10 experts. Utilising this approach allowed the researcher to focus on experts’ knowledge and experiences based on the issues explored. Data were analysed using thematic analysis with pencil and paper, while Microsoft Excel was used as a tool for data keeping. The study identified five main criteria for sustainability which includes i) specialization; ii) work-based design; iii) dynamic; iv) interactive teaching and learning, and v) international syllabus. It is expected that the outcome of this study will contribute towards the sustainability of TVET Teacher Education programmes in Malaysia thus improving the quality of TVET graduates to achieve the national goal of becoming a high-income nation.